Control Modes Comparison Results Focused on Real Heat Exchanger System Response - Hanafi, Dirman; A.A. Emhemed, Abdulrahman (International Journal of Integrated Engineering, 2011)
This paper focus on the heat exchanger system temperature control design based on mathematical model. The mathematical model is constructed using dynamics and real parameters of the heat exchanger. The heat exchanger model is QAD MODEL BDT921. Two types of control are applied; they are Proportion Integral Derivative (PID) controller and Fuzzy Proportional (FD) controller. PID is a generic control loop feedback mechanism attempts to correct the error between a measured process variable and a desired set point by calculating and then outputting a corrective action. While FD is a controller that it base on the logical of the human expert. The two controllers are simulated using Matlab Simulink software. The results show that FD controller response better than PID controller. It means FD controller is a suitable control to improve the performance of the heat exchanger QAD MODEL BDT921 model.